A powerful combination of quadruple isotope dilution strategy with dispersive magnetic solid phase extraction for the accurate and precise multi-analyte determination of tadalafil, sildenafil, avanafil and vardenafil in human plasma and urine samples using LC-ESI-Tandem MS - Er, Elif Ozturk; Akkaya, Erhan; Ozbek, Belma; Bakirdere, Sezgin (ELSEVIER, 2020)
Trace organic analysis in biological matrices plays a critical role in clinical studies. To achieve a reliable evaluation of clinical practice, many analytical improvements have been introduced to overcome the difficulties/errors in the steps of the analysis procedure. In this study, quadrupole isotope dilution mass spectrometry was combined with dispersive magnetic solid phase extraction to achieve inherent accuracy and precision at trace levels. The lower limits of detection and quantification values of analytes ranged between 0.42-0.84 ng/g and 1.39-2.80 ng/g, respectively with percent relative standard deviations (%RSDs) of 0.65-1.24%. The combined method was applied for simultaneous determination of selected erectile drugs including sildenafil, tadalafil, vardenafil and avanafil in human urine and plasma samples by using commercially available isotopic analogues of these compounds. Great percent recovery values between 97.50-99.57% and 98.26-100.92% with%RSDs of 1.19-1.96% and 0.49-1.95% respectively for plasma and urine samples were obtained. The proposed method is simple, environmentally friendly, requires less laborious sampling and provides superior accuracy and precision at low levels of analytes. Furthermore, the proposed method also provides economical advantages. The synthesis procedure of magnetic sorbent is easy, low cost and does not require high consumption of toxic chemicals. Additionally, the isotopically enriched standards of target compounds are accessible, do not have high costs and the method requires only small amounts of these chemicals.
Keywords: Quadrupole Isotope dilution; Tandem mass spectrometry; Magnetic solid phase extraction; Erectile drugs; MASS-SPECTROMETRY; DIETARY-SUPPLEMENTS; UHPLC-MS/MS; DERIVATIZATION; METABOLITES; LC/MS/MS; BLOOD; SERUM; Chemistry